Resenhas - Clasen Lorenzet, Elisa; Mena Alves, Letícia; da Costa Olioni, Raymundo; Nayar Oliveira Lourenço, Circi; Lazzarotto, Cristiane; Brasil Irala, Valesca (Revista Linguagem & Ensino, 2019)
Esta seção contém resenhas de seis livros.